Hubungan Pengetahuan, Sikap Dan Dukungan Keluarga Dengan Perilaku Hidup Bersih Dan Sehat Pada Remaja Di SMK Kesehatan Aras Depok Tahun 2024 - Indriani Adam; Eka Bati Widyaningsih; Nirmala Harahap (Indonesian Journal of Midwifery Scientific, 2025)
The Correlation of Knowledge, Attitude, and Family Support with Clean and Healthy Living Behavior in Adolescents at SMK Kesehatan Aras Depok in 2024. Health is a state where our bodies are free from disease, as well as a state of well-being in ourselves both mental, physical, and social conditions. Based on the data above, the researcher conducted a preliminary study at SMK Aras where the results of interviews with several SMK children said that there were still fewer who implemented clean and healthy living behaviors. One of the objectives of this study was to determine the relationship between knowledge, attitudes and family support with clean and healthy living behavior in adolescents. This type of research is quantitative, survey type of research with descriptive, and analytic research. This research design is crossectional. The research sample taken was adolescent students who attended SMK Kesehatan Aras Depok in 2024 with a total of 84 people. The data used is primary data. Data collection methods used in a study are observation (closed and open), interviews, and questionnaires. Based on the results of the study, it was found that most of the respondents who had an unfavorable attitude had poor clean and healthy living behavior as many as 29 respondents (72.5%). This research is in line with Finni's research in 2019 where there is a significant relationship between attitude and clean and healthy living behavior (PHBS) of students expressed through the odds ratio = 6.750, which means that students who have a good attitude have a 6 times chance of doing good clean and healthy living behavior in everyday life.